The dyslexia checklist : a practical reference for parents and teachers - Rief, Sandra F.; Stern, Judith M. (San Francisco, Calif. : Jossey-Bass, 2010)
The book is filled with the most current research available on dyslexia, and contains a wealth of practical strategies, supports, and interventions.
Basic information on dyslexia -- Strategies for helping with reading, language, and writing -- Checklists for parents -- Checklists for teachers -- Other important checklists for parents and teachers.
Includes bibliographical references and index.
Keywords: Dyslexic children -- United States -- Education; Learning disabled children -- Education -- United States; Dyslexic children -- United States -- Education -- Case studies